The types and levels of physical activity and sedentary behaviour of Senior Phase learners in Potchefstroom - Johanna C.W. De Vos; Dorita Du Toit; Dané Coetzee (AOSIS, 2016)
Background: Worldwide, the health risks of decreasing physical activity levels and increasing sedentary behaviour among adolescents are a raising concern. Objective: To determine the types and levels of physical activity as well as that of sedentary behaviour of a group Senior Phase learners in South Africa. Methods: The adapted Children's Leisure Activities Study Survey (CLASS) questionnaire was used for determining the types and levels of physical activity and sedentary behaviour of 230 Grade 7 learners, from three schools in Potchefstroom. Data were analysed by means of the SAS statistics programme, and descriptive statistics, as well as independent t-tests andeffect sizes (ES) were used. Results: Moderate to high-intensity physical activity levels of between 334 and 361 min per week were found, and sedentary behaviour of between 3077 and 3410 min per week, which implies that between 70.7% and 71.9% of the participants, did not meet the recommended health-based guidelines. Higher activity levels were shown during weekends, where the boys were significantly more active than girls (p < 0.001; ES between 0.21 and 0.56), and girls showed more sedentary behaviours than the boys (ES between 0.18 and 0.20). The leisure time physical activities with the highest participation were soccer, recreational swimming, jogging and dancing, while the sedentary activities were listening to music, riding a vehicle and being busy on the phone. Conclusion: Strategies need to be implemented to raise the physical activity levels of Senior Phase learners, especially during weekdays, and to decrease sedentary behaviour. With this view in mind, recommendations are made for Physical Education teachers.